Assessment of seed qualities in relation to storage materials used in ethnic communities of Moulvibazar district (Journal of the Sylhet Agricultural University, 2025)
Quality seeds are very important for successful crop production. Manipuri, Khasia and Garo ethnic communities cultivate different types of crops in their farmlands and save their own seeds traditionally which are quite different from general farmers. Quality analyses of farmer’s saved seeds of ethnic communities have not been studied. Therefore, the experiment was designed to study the seed storage technologies used by ethnic communities. A total of 29 seed samples collected where 15 seed samples from the Manipuri, 4 from the Khasia, and 10 from the Garo ethnic communities to determine seed quality especially purity, germination, planting value of seed (PVS). In seed samples of the Manipuri community, the percentage germination, purity, and planting value of seeds (PVS) varied from 1.5% to 97.0%, 98% to 99%, and 0.5% to 94.1%, respectively. The highest germination (97.0%), purity (99.0%), and PVS (94.1%) were found in rice BRRI dhan 94 (Ranjit dhan) seed samples and the lowest germination (1.5%) and PVS (0.5%) was found in okra seed samples. The highest normal seedlings (95%) were also found in the rice (Ranjitdhan) seed sample. In seed samples collected from the Khasia community, germination percentage ranged from 3.3% to 93.8% whereas purity and PVS ranged from 98% to 99% and 1.7% to 91.1%, respectively. The highest germination was found in sponge gourd (93.8%) along with the highest normal seedlings (92.0%) and the lowest was found in country bean (3.3%). The highest PVS was found in sponge gourd (91.1%) followed by long yard bean (85.9%) and lai shak (80.4%) and the lowest were found in country bean (1.7%). In Garo communities, the purity percentage of seed samples ranged from 98% to 99% whereas germination percentage varied from 2.5% to 98.5%. The highest germination was found in okra seed (98.0%) whereas the lowest germination (2.5%) was in french bean and wax gourd, respectively. PVS was calculated which varied from 1.2% to 95.5%. The highest PVS was recorded in okra seed (95.5%) followed by lai shak (78.9%). The lowest PVS (1.2%) was in french bean and wax gourd. The highest normal seedlings were produced from okra seed samples (96.5%). A total of 14 fungi representing 12 genera were detected to be associated with the 15 seed samples collected from Manipuri ethnic community; 7 fungi representing 5 genera were detected from the seed samples of Khasia community and 9 fungi representing 8 genera were detected from seed samples of Garo community. The storage techniques used by three ethnic communities, keeping seeds in gunny bags, glass bottles, and cloth bags are suitable for the storage of seed samples. Fumigation was found to be good for keeping away from storage fungi and maintaining the quality of seeds, especially germination.J. Sylhet Agril. Univ. 11(1): 17-30, 2024